2017
DOI: 10.1253/circj.cj-17-0193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ezetimibe on Stabilization and Regression of Intracoronary Plaque ― The ZIPANGU Study ―

Abstract: (IVUS), respectively, in the TWINS 3 and TOGETHAR 4 studies.In the present ZIPANGU (ezetimibe clinical investigation for regression of intracoronary plaque evaluated by angioscopy and ultrasound) study, we compared the effect of combination therapy (statin+ezetimibe) and monotherapy (statin alone) through examination of the plaque stabilization effect by angioscopy and the plaque regression effect by IVUS. Methods Study DesignThis study was a multicenter, prospective, randomized, L ow-density lipoprotein chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
(10 reference statements)
0
15
0
1
Order By: Relevance
“…Ezetimibe ameliorates endothelial dysfunction and atherosclerosis regression in coronary arteries [126]. Results from an ezetimibe clinical investigation on the regression of intracoronary plaque evaluated by angioscopy and ultrasound (ZIPANGU) in patients with stable CVD have suggested that ezetimibe and atorvastatin are more effective for plaque regression than statin alone [165]. Antibodies against proprotein convertase subtilisin/kexin type 9 (PCSK9) are used to lower LDL in the management of atherosclerotic CVD risk [161,164].…”
Section: Potential Therapies For Promoting Plaque Regressionmentioning
confidence: 99%
“…Ezetimibe ameliorates endothelial dysfunction and atherosclerosis regression in coronary arteries [126]. Results from an ezetimibe clinical investigation on the regression of intracoronary plaque evaluated by angioscopy and ultrasound (ZIPANGU) in patients with stable CVD have suggested that ezetimibe and atorvastatin are more effective for plaque regression than statin alone [165]. Antibodies against proprotein convertase subtilisin/kexin type 9 (PCSK9) are used to lower LDL in the management of atherosclerotic CVD risk [161,164].…”
Section: Potential Therapies For Promoting Plaque Regressionmentioning
confidence: 99%
“…[ 23 ] However, whether the combination therapy had a superior effect on stabilizing coronary VP, especially increasing the FCT remains unclear. [ 24 26 ] Few studies have evaluated the effect of combination therapy on the FCT of VPs. One study showed that when ezetimibe was combined with statin, it could further increase the FCT more than statin monotherapy [ 27 ] ; this finding is similar to our result.…”
Section: Discussionmentioning
confidence: 99%
“…Ezetimibe decreases small intestine cholesterol absorption by inhibiting the Niemann-Pick C1-Like 1 (NPC1L1) transporter [172,177]. While the exact mechanisms of the effect of ezetimibe on atherosclerosis by itself are not as well defined as the effects of statins on atherosclerotic plaque progression and stabilization, the addition of ezetimibe to statins has been shown to regress plaque burden, reduce plaque volume, and promote plaque stabilization [178,179]. PSCK9 works by interacting in with hepatic LDLR and enhancing the degradation of the receptor by hepatic lysosomes, with PSCK9 inhibitors thus mitigating the PSCK9-mediated turnover of hepatic LDLR and prolonging LDLR lifespan and uptake of circulating LDL-C [180].…”
Section: Nonstatinsmentioning
confidence: 99%